Prevalence of asymptomatic bacteriuria and its antibiotic susceptibility pattern among pregnant women in Patan Hospital: a descriptive study - Mahaseth, Ashika; Shahi, Smriti; Twanabasu, Sajal; Sharma, Paban; Singh, Alka; Maskey, Sujina (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Asymptomatic bacteriuria (ASB) is common during pregnancy. ASB is a risk factor for adverse perinatal outcomes and maternal complications. The gold standard for detecting bacteriuria is urine culture. Therefore, a routine urine culture should be done in pregnant women to screen for bacteriuria at the first antenatal visit. This study was conducted to determine the prevalence of ASB, the most common organism, and its antibiotic sensitivity pattern at Patan Hospital. Method: This descriptive study was conducted from November 1, 2020, to October 31, 2021. All pregnant women visiting the Patan Hospital antenatal clinic who fulfilled the inclusion criteria were enrolled after obtaining written consent. After taking the patient’s history and conducting an examination, proper instructions were given to collect a urine sample, which was then sent for culture and sensitivity testing. The report was collected, and treatment was provided accordingly. Data were collected, and descriptive analysis was done. Result: Among 122 pregnant women, the prevalence of asymptomatic bacteriuria was 10.6%. Escherichia coli was found to be the most prevalent organism to cause asymptomatic bacteriuria, followed by Klebsiella pneumoniae. These organisms were 100% sensitive to imipenem and meropenem, but least sensitive to ampicillin. Conclusion: Early screening, identification of the infecting organism, and antibiotic sensitivity testing are important interventions to prevent complications to both the pregnant woman and the fetus.